The sounds of fish off Cape Naturaliste, Western Australia - Parsons, Miles; McCauley, Robert; Thomas, Frank (Australian Acoustical Society, 2013)
Fish calls and choruses contribute considerable energy to the underwater soundscapes of Western Australia's waters. There are many fish species of social and economic importance which could be the source of these sounds. For example, the Western Australian dhufish (Glaucosoma hebraicum), which is endemic to the coast, has been shown to produce sound when captured. To investigate how much this species contributes to ambient noise levels, loggers were deployed between December, 2011and February, 2012 at numerous locations around Cape Naturaliste in Western Australia, where some of the largest numbers of G. hebraicum are reported. Recordings taken near the site of the HMAS Swan wreck between 2009 and 2010 were also examined. Five fish choruses have been described centred at approximately 0.5, 1, 2 and >2 kHz (two choruses at >2 kHz). Many individual fish calls were detected at various locations around the Cape, particularly in the frequency ranges between100 and 900 Hz. The acoustic characteristics of these calls are described, as well as the contribution of fish calls and choruses to the local soundscapes. The calls most similar to the previously reported G. hebraicum calls have been identified.